2015
DOI: 10.1186/s13046-015-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-4 expression contributes to tumor proliferation, angiogenesis and patient prognosis in human pancreatic cancer

Abstract: BackgroundNectin-4 belongs to the nectin family that has diverse physiological and pathological functions in humans. Recent studies have also suggested some roles for Nectin-4 in several human cancers. However, the precise roles and clinical relevance of Nectin-4 in tumors are largely unknown.MethodsNectin-4 expression was investigated in 123 patients with pancreatic cancer by immunohistochemistry. Furthermore, we investigated the association of Nectin-4 in pancreatic cancer with tumor proliferation, angiogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 43 publications
5
110
0
Order By: Relevance
“…Nectin-4 plays a role in the formation and maintenance of adherens junctions in cooperation with cadherins [24][25][26][27] . Other scholars have revealed that nectin-4 is re-expressed as a tumourassociated antigen with pro-oncogenic properties in various carcinomas [28][29][30]. In our previous study [31] , Nectin-4 is critical for GBC proliferation and invasion via activating PI3K/AKT pathway.…”
Section: Discussion 10mentioning
confidence: 69%
“…Nectin-4 plays a role in the formation and maintenance of adherens junctions in cooperation with cadherins [24][25][26][27] . Other scholars have revealed that nectin-4 is re-expressed as a tumourassociated antigen with pro-oncogenic properties in various carcinomas [28][29][30]. In our previous study [31] , Nectin-4 is critical for GBC proliferation and invasion via activating PI3K/AKT pathway.…”
Section: Discussion 10mentioning
confidence: 69%
“…It has been reported that nectin‐4 expression correlated significantly with levels of both ki67 and vascular endothelial growth factor expression, which suggests that nectin‐4 expression contributes to tumor proliferation and angiogenesis . Actually, patients with a high nectin‐4 expression level had a poorer postoperative prognosis than those with low expression in human pancreatic cancer . Therefore, rMV‐SLAMblind is expected to contribute to treatment of malignant cancer.…”
Section: Discussionmentioning
confidence: 99%
“…a). Conversely, it has been reported that nectin‐4 was strongly expressed in 69/123 clinical samples from pancreatic cancer patients . Therefore, rMV‐SLAMblind has the potential to be therapeutically applicable to approximately half of pancreatic cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the expression of nectin-3 is upregulated in lung adenocarcinoma (Maniwa et al 2012) and ovarian, colorectal, and peritoneal endometriotic tissues (Ballester et al 2012). The expression of nectin-4 is upregulated in breast carcinoma tissues (Athanassiadou et al 2011;Fabre-Lafay et al 2005;Pavlova et al 2013), non-small-cell lung cancer tissues (Takano et al 2009), ovarian cancer tissues (Derycke et al 2010), pancreatic cancer tissues (Izumi et al 2015;Nishiwada et al 2015), and eutopic endometrium tissues with endometriosis (Ballester et al 2012). Nectin-2 is involved in cancer immunity by modulating the signaling cascade in certain T cells and NK cells (Pende et al 2005;Stanietsky et al 2009).…”
Section: Cancermentioning
confidence: 99%